2023
DOI: 10.1101/2023.10.23.23297403
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of spatial connectivity on NPIs effectiveness

Chiara E. Sabbatini,
Giulia Pullano,
Laura Di Domenico
et al.

Abstract: Background. France implemented a combination of non-pharmaceutical interventions (NPIs) to manage the COVID-19 pandemic between September 2020 and June 2021. These included a lockdown in the fall 2020 - the second since the start of the pandemic - to counteract the second wave, followed by a long period of nighttime curfew, and by a third lockdown in the spring 2021 against the Alpha wave. Interventions have so far been evaluated in isolation, neglecting the spatial connectivity between regions through mobilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…These include spatial differences in variants' penetration 48,49 and the application of social distancing restrictions in our scenario analyses. We note however that non-pharmaceutical interventions were always applied nationwide in France, with limited exceptions 50 .…”
Section: Discussionmentioning
confidence: 94%
“…These include spatial differences in variants' penetration 48,49 and the application of social distancing restrictions in our scenario analyses. We note however that non-pharmaceutical interventions were always applied nationwide in France, with limited exceptions 50 .…”
Section: Discussionmentioning
confidence: 94%
“…A later curfew starting at 8 pm was less effective, but both types of curfew lost efficacy with time of application, suggesting pandemic control fatigue in the population. Their calculation showed that stop‐and‐go lockdowns (intercut with periods of no restrictions) could have achieved a 40% reduction of hospitalizations for a similar number of effective days under restrictions (Sabbatini et al., 2024). The lower efficacy of curfew (5% case reduction) compared to lockdown (90% case reduction) was also observed in Luxembourg (Thompson & Wattam, 2021).…”
Section: Looking Backwards: the Efficacy Of Npi Measures On The Covid...mentioning
confidence: 99%